Marketing mix strategy for MICE in preparation for meeting package sales in Bintang Bali Resort in the new normal era - Ni Luh Putu Agustina Darmayanti; I Ketut Surata; Chintia Pinaria (Journal of Applied Sciences in Travel and Hospitality, 2022)
The aims of this study are to (1) analyze the MICE marketing mix strategy in selling meeting package planned by Bintang Bali Resort in the new normal and (2) formulate the MICE marketing mix strategy in preparing the meeting package sales at Bintang Bali Resort in the new normal. This study uses three key informants consisting of Assistant Director of Sales and Marketing Bintang Bali Resort, Account Director of The Westin Resort Nusa Dua Bali and Assistant Director of Event Services Bali Nusa Dua Convention Center. Data collection techniques used are observation, in-depth interviews and documentation studies. Data analysis techniques used are data reduction, data presentation, drawing conclusions and testing the validity of the results with source triangulation. Based on the analysis  done, there  are two results showed, The first (1) the MICE marketing mix in planning the sales of meeting pckage on the new normal at Bintang Bali Resort was mostly well implemented. The second (2) Bintang Bali Resort needs to implement product strategies in the form of digital innovations such as procurement of hybrids and virtual meetings, utilizing digital promotion systems on social media to the fullest, making variations of meeting package based on hotels/venue comparisons can be improved in the future and pay attention to products with system using 4 R (reuse, reduce, recycle and replace) in sustainable environmental aspects in the new normal.